Carpal tunnel syndrome related to antebrachial Cimino-Brescia fistula. Issue 5 (May 1977) - Harding, A E; Le Fanu, J
Abstract : Two patients are described in whom symptoms of the carpal tunnel syndrome were provoked by haemodialysis for which an antebrachial arteriovenous fistula had been established. The symptoms in one case were partially relieved by ligation of the radial artery distal to the fistula, and in both they were abolished by decompression of the median nerve by section of the flexor retinaculum at the wrist. There is evidence that the median nerve is abnormally susceptible to ischaemia in the carpal tunnel syndrome, and it is suggested that in these patients the symptoms were provoked by a vascular steal mechanism related to the fistula.